All is true [videorecording (DVD)] - Branagh, Kenneth; Branagh, Kenneth; Branagh, Kenneth; McKellen, Ian; Dench, Judi, 1934-; Wilson, Lydia, 1984- (Sony Pictures Home Entertainment, 2019)
A look into the last years of William Shakespeare's life.